PENGEMBANGAN “DIGITAL INTERACTIVE STORYTELLER” BERBASIS ANDROID UNTUK TUNANETRA - Anak Agung Istri Ita Paramitha; Made Windu Antara Kesiman; I Ketut Resika Arthana (Universitas Pendidikan Ganesha, 2014)
Storytelling is an art which can be done either with tools or not to convey message, information or entertaining story. Storytelling has many benefits for child development; one of them is to increase child’s imagination. “Digital Interactive Storyteller” is an application using Android devices that intended for blind user. This research aims to design and implement “Digital Interactive Storyteller” an Android-based Application for Blind People.Development of the Digital Interactive Storyteller” an Android-based Application for Blind People is using the software development life cycle SDLC (Software Development Life Cycle) with the waterfall model. The main feature in this application is an interactive audio story using Android devices. Interactive here means the users can choose their own storyline.The result of this research is the design and implementation of the Digital Interactive Storyteller” an Android-based Application for Blind People that has been successfully carried out. The design is done by using a functional model of the UML (Unified Modeling Language). Implemented in Java programming language using the Eclipse editor and ADT (Android Development Tools). The entire functional requirements have been successfully implemented in accordance with the design.